Diagnosis methods for mechanisms and machines based on empirical mode decomposition of a vibrosignal and the wilcoxon test - Zuev, Andrey; Ivashko, Andrey; Lunin, Denis (Національний технічний університет "Харківський політехнічний інститут", 2022)
Methods for diagnosing mechanisms and machines based on the analysis of vibration signals are considered. In particular, the comparison of various algorithms for analyzing vibration signals in the time and frequency domains was made, methods for selecting diagnostic features and methods for secondary processing were analyzed. The purpose of the study is to develop algorithms for selecting the vibration signal envelope based on empirical mode decomposition and decomposition of the signal into intrinsic mode functions, algorithms for the spectral estimation of envelopes and to choose a criterion for making a decision on object classification. It is proposed to choose the non-parametric Wilcoxon signed-rank test to determine the statistical significance of the difference between the parameters of normal and faulty objects. The multichannel microcontroller system for collecting data from an accelerometer and transmitting it to a computer via a local Wi-Fi network, including a number of independent data gathering nodes connected to a common distributed computing system, has been developed and experimentally studied. The computer processing of the recorded vibration signals for serviceable and faulty mechanisms was performed, including data decoding, Hilbert-Huang transform, spectral analysis using the Welch and Yule-Walker methods, and the choice of a diagnostic feature that provides maximum reliability of recognition. Based on the results of the work, it was determined that the empirical mode decomposition makes it possible to obtain vibration signal envelopes suitable for further diagnostics. Recommendations are developed for choosing the intrinsic mode function and the spectral analysis algorithm, it is determined that the first intrinsic mode function is the most informative for the mechanism under study. In accordance with the Wilcoxon criterion, the degree of diagnostic reliability was numerically determined in the analysis of the spectral power density of the vibration signal and the amplitude of peaks, and the comparison of probabilities of error-free recognition for various modifications of the algorithm was made.

Розглянуто методи діагностики механізмів та машин на основі аналізу вібросигналів. Зокрема, виконано порівняння різних алгоритмів аналізу вібросигналів у часовій та частотній області, проаналізовано методи виділення діагностичних ознак та методи вторинної обробки. Метою дослідження є розробка алгоритмів виділення огинаючої вібросигналу на основі емпіричної модової декомпозиції та розкладання сигналу на внутрішні модові функції, алгоритмів спектрального оцінювання огинаючих та вибір критерію для ухвалення рішення про класифікацію об'єкта. Запропоновано вибрати непараметричний тест Уілкоксону для визначення статистичної значущості різниці між параметрами справного та бракованого об'єктів. Розроблено та експериментально досліджено багатоканальну мікроконтролерну систему знімання даних з акселерометра та передачі в комп'ютер по локальній мережі Wi-Fi, що включає ряд незалежних модулів збору даних, з'єднаних у загальну розподілену обчислювальну систему. Виконано комп'ютерну обробку знятих вібросигналів для справних та несправних механізмів, що включає декодування даних, перетворення Гільберта-Хуанга, спектральний аналіз методами Уелча та Юла-Уолкера та вибір діагностичної ознаки, що забезпечує максимальну достовірність розпізнавання. За результатами роботи визначено, що емпірична модова декомпозиція дозволяє отримувати огинаючі вібросигналів, придатні для подальшої діагностики. Розроблено рекомендації щодо вибору внутрішньої модової функції та алгоритму спектрального аналізу, визначено, що максимально інформативною для досліджуваного механізму є перша внутрішня модова функція. Відповідно до критерію Уілкоксона чисельно визначено ступінь достовірності діагностики при аналізі спектральної щільності потужності вібросигналу та амплітуди піків та проведено порівняння ймовірностей безпомилкового розпізнавання для різних модифікацій алгоритму.
Методи діагностики механізмів і машин на основі емпіричної модової декомпозиції вібросигналу і теста Уілкоксона
Keywords: vibration signal; microcontroller; accelerometer; spectral analysis; empirical mode decomposition; Hilbert-Huang transform; intrinsic mode functions; Wilcoxon test; вібросигнал; акселерометр; спектральний аналіз; емпірична модова декомпозиція; перетворення ГільбертаХуанга; внутрішні модові функції; критерій Уілкоксона; мікроконтролер